Optimasi Kondisi Operasi Proses Elektroplating Nikel-Khrom Untuk Ketahanan Korosi Baja Profile L - Mad Yusup; Diyaa Aaisyah Salmaa Putri Atmaja; Purbawati Purbawati; Ida Rosanti (International Forum of Researchers and Lecturers, 2025)
This research aims to optimize the operating conditions of nickel-chrome electroplating to increase the corrosion resistance of L profile steel materials. Nickel-chrome electroplating is a metal coating method used to protect steel surfaces from corrosion and improve the aesthetic appearance. The electroplating process involves several variables such as solution concentration, temperature, current density, and plating time. In this research, various operating conditions were optimized to obtain maximum corrosion resistance. The experimental method was carried out with variations of these parameters and the results were evaluated using corrosion tests and microscopic analysis. The research results show that certain operating conditions produce a protective layer that is more effective in preventing corrosion on L profile steel. This optimization is expected to make a significant contribution in industrial applications that require high corrosion protection.